Vulnerability Level of Small-scale Fishery Enterprises in Central Tapanuli, North Sumatra - Sitompul, Nabila Khairiyah; Wiyono, Eko Sri; Solihin, Iin (Institut Pertanian Bogor, 2025)
Numerous operational variables constantly threaten small-scale fishery enterprises, increasing vulnerability and the possibility of economic stagnation. The goal of this study was to investigate the vulnerability of small-scale fishery enterprises in Central Tapanuli Regency. The study looked at six aspects of vulnerability: natural, human, physical, financial, social, and institutional. The methodology employed was participative, using interviews, observations, and Likert scale questionnaires. The study's findings revealed that seasonal and weather circumstances were the most significant weaknesses affecting fishery enterprises. Except for the marketing group, which showed a greater degree of vulnerability was visible in terms of institutional supporting and participation by fishermen's groups. Finally, fishery enterprises can improve their resilience by developing business groups and implementing treatments tailored to each group's individual needs. This study proposes technical methods to increase the resilience and sustainability of the region's fisheries enterprises. Keywords: Central Tapanuli, fisheries business, resilience, vulnerability